Does small volume metastatic lymph node disease affect long-term prognosis in early cervical cancer?. Issue 3 (March 2020) - Nica, Andra; Gien, Lilian T; Ferguson, Sarah Elizabeth; Covens, Allan
Abstract : Introduction: As sentinel lymph node biopsy is evolving to an accepted standard of care, clinicians are being faced with more frequent cases of small volume nodal metastatic disease. The objective of this study is to describe the management and to measure the effect on recurrence rates of nodal micrometastasis and isolated tumor cells in patients with early stage cervical cancer at two high-volume centers. Methods: We conducted a review of prospectively collected patients with surgically treated cervical cancer who were found to have micrometastasis or isolated tumor cells on ultrastaging of the sentinel lymph node. Our practice is to follow patients for ≥5 years post-operatively either at our center or another cancer center closer to home. Results: Nineteen patients with small volume nodal disease were identified between 2006 and 2018. Median follow-up was 62 months. Ten (53%) had nodal micrometastatic disease, while nine (47%) had isolated tumor cells detected in the sentinel lymph node. Seven patients (37%) underwent completion pelvic lymphadenectomy and four of them also had para-aortic lymphadenectomy; there were no positive non-sentinel lymph nodes. The majority (74%) received adjuvant treatment, mostly driven by tumor factors. We observed two recurrences. Recurrence-free survival was comparable with historical cohorts of node negative patients, and adjuvant treatment did not seem to impact the recurrence rate (p=0.5). Conclusion: Given the uncertainties around the prognostic significance of small volume nodal disease in cervical cancer, a large proportion of patients receive adjuvant treatment. We found no positive non-sentinel lymph nodes, suggesting that pelvic lymphadenectomy or para-aortic lymphadenectomy may not be of benefit in patients diagnosed with small volume nodal metastases. Recurrence-free survival in this group did not seem to be affected. However, given the small numbers of patients and lack of level 1 evidence, decisions should be individualized in accordance with patient preferences and tumor factors.